A school-based intervention associated with improvements in cardiometabolic risk profiles in young people with intellectual disabilities. (March 2013) - Wallén, Eva Flygare; Müllersdorf, Maria; Christensson, Kyllike; Marcus, Claude
This study evaluates a multifactorial school-based intervention with the aim of decreasing cardiometabolic risk factors by means of a healthy lifestyle, primarily with daily physical activity and healthy food during school hours, at an upper secondary school for students with intellectual disabilities. The outcome is measured in terms of cardiometabolic risk factors and cardiovascular fitness, both known to increase the risk of future cardiovascular disease, type 2 diabetes and cancer. Two years of intervention resulted in a positive trend in several measured cardiometabolic risk factors, with no increase in fat mass. Cardiovascular fitness levels were unchanged. We conclude that a healthy school environment can contribute to a deceleration of both fat mass gain and loss of cardiovascular fitness.